Evaluation of methodologies for identifying gynaeceum and androecium in rice as target tissues of Burkholderia glumae (Burkholderiaceae) - Guzman Arce, Karent Sofia; Mosquera, Gloria; Molina Henao, Yherson Franchesco (2025)
The specificity of Burkholderia glumae for reproductive tissues was studied through three types of inoculations. In these inoculations, the tissues of the gynoecium and androecium were evaluated separately in two rice genotypes. The experiments were conducted under controlled greenhouse conditions during the months of April and August 2024. Gynoecium inoculation allowed for the evaluation of grain formation from emasculated flowers inoculated with B. glumae. On the other hand, androecium inoculation enabled the assessment of the proportion of calli formed from anthers in inoculated medium. Lastly, a direct inoculation was performed through the roots of tillers to evaluate grain formation and the presence of symptoms. The results demonstrated that for gynoecium inoculation, there were differences between treatments and genotypes; however, the interaction between these factors did not show significant differences. Conversely, for androecium inoculation, no calli were formed from inoculated anthers in any of the evaluated genotypes. Finally, in root inoculation, no symptoms were observed, and B. glumae was not detected at the molecular level. According to the results obtained in this study, the gynoecium inoculation methodology allows differentiation in susceptibility between genotypes regarding B. glumae infection, in contrast to the other methodologies, in which no significant variations were observed between genotypes.